Pemberdayaan Bumdes Desa Cibubuan Guna Peningkatan UMK (Usaha Mikro dan Kecil) Menuju Kemandirian Ekonomi Masyarakat Desa - Imas Rosidawati Wiradirja; Hennie Husniah; Nunung Hastika Ardiwidjaya; Nungki Heriyati (UNISBA Press, 2024)
Abstract. BUMdes (Village-Owned Enterprise) is a village business institution managed by the community and village government in an effort to strengthen the village economy and is formed based on the needs and potential of the village. Even though it has been supported by several regulations such as Law no. 6 of 2014 concerning Villages Article 1 Paragraph (6) and Republic of Indonesia Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises, however, the existence of BUMdes is still not fully up to expectations. The existence of BUMdes in Cibubuan Village, Conggeang District, Sumedang Regency is different, this BUMdes is the main supporter of the existence of Cibubuan Village MSEs in the One Village One Product (OVOP) project where this BUMdes has the main program, namely providing all the material needs for MSEs' products in making opak as One Village One Product. The aim of the PKM Professor of LLDIKTI Region IV West Java together with students from Langlangbuana University (UNLA) and students from the Indonesian Computer University (UNIKOM) is to increase community economic empowerment through BUMdes. The process of empowering Bumdes in Cibubuan Village is directed at helping product marketing, assisting with licensing, partnerships with various parties and strengthening institutions. The existence of BUMdes in Cibubuan Village is expected to be an institution that makes it easier to access business capital, increases community production which can directly increase community income. Abstrak. BUMdes (Badan Usaha Milik Desa) merupakan sebuah lembaga usaha desa yang dikelola oleh masyarakat dan pemerintah desa dalam upaya memperkuat perekonomian desa serta dibentuk berdasarkan kebutuhan dan potensi desa. Walaupun sudah didukung beberapa regulasi seperti UU No. 6 Tahun 2014 tentang Desa Pasal 1 Ayat (6) dan Peraturan Pemerintah Republik Indonesia Nomor 11 Tahun 2021Tentang Badan Usaha Milik Desa, namun keberadaan BUMdes masih belum sepenuhnya sesuai harapan. Keberadaan BUMdes Desa Cibubuan Kecamatan Conggeang Kabupaten Sumedang berbeda , BUMdes ini menjadi pendukung utama keberadaan UMK Desa Cibubuan dalam proyek One Village One Product (OVOP) dimana BUMdes ini memiliki program utama yaitu menyediakan semua kebutuhan bahan produk UMK dalam pembuatan opak sebagai One Village One Product. Tujuan dari PKM Guru Besar LLDIKTI Wilayah IV Jawa Barat bersama mahasiswa dari Universitas Langlangbuana (UNLA) dan mahasiswa Universitas Komputer Indonesia (UNIKOM) ini untuk peningkatan Pemberdayaan ekonomi masyarakat melalui BUMdes. Proses pemberdayaan Bumdes di Desa Cibubuan diarahkan untuk membantu pemasaran produk , membantu perijinan , kemitraan dengan berbagai pihak serta penguatan kelembagaan. Adanya BUMdes di Desa Cibubuan diharapkan sebagai lembaga yang mempermudah kepada akses modal usaha, meningkatnya produksi masyarakat yang secara langsung dapat meningkatkan pendapatan masyarakat.